Comparison Between Efficacy and Safety of Oral Azithromycin (250mg) vs Oral Doxycycline (100mg) in Treatment of Meibomian Gland Dysfunction (MGD) - Yousuf, Waseem; Humayun, Fakhar; Janjua, Teyyeb Azeem; Khan, Taimoor Ashraf; Sarfraz, Muhammad Haroon; Mehboob, Mohammad Asim (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the efficacy and safety of oral Azithromycin with oral Doxycycline in patients with Meibomian Gland Dysfunction. Study Design: Quasi-experimental study. Place and Duration of the Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Apr 2021 to Apr 2022. Methodology: The sample population comprised 172 subjects, including 86 cases in the oral Doxycycline-Group and 86 oralAzithromycin-Group. Meibomian Gland Dysfunction was diagnosed by a consultant ophthalmologist by slit-lampexamination. Schirmer-I test and Tear Break Up Time were performed. Signs and symptoms of Meibomian Gland Dysfunction were assessed before treatment and at six months follow-up. Results: The study recruited equal numbers of cases and controls. Symptoms scores for burning sensation (2.04±0.5 vs 1.9±0.7) and foreign body sensation (1.8±0.6 vs 1.5±0.8) were significantly higher in patients taking Doxycycline as compared to the Azithromycin-Group (p<0.05). On comparing the signs score between the two Groups, it was seen that total scores (pretreatment and post-treatment) were more significant in the Doxycycline-Group (p<0.05). Treatment with Doxycycline yielded more significant complications, such as diarrhoea (39.5%), nausea (46.5%), and cramps (48.8%). Headache was more associated with Azithromycin treatment (3.4%), whereas Rash (1.1%) and blurring of vision (1.1%) were seen in the Doxycycline-Group. Conclusion: Meibomian Gland Dysfunction leads to tear film instability and direct damage to the ocular surface epithelium. This study supports the clinical efficacy and safety of oral Azithromycin and Doxycycline therapy for managing refractory or severe Meibomian gland disease.